Opening data with trust: Reflections on a holistic approach to data governance at IFPRI - Yerramareddy, Indira; Prasai, Nilam; Saito, Erica; Plummer, Leigh; Bayeh, Mulugeta; Shang, Xinyuan; Miller, Ryan; Jung, Yunchul (American Geophysical Union, 2020)
IFPRI’s experience building overall data governance for Research Data Management (RDM) has helped us to build trust among IFPRI staff for opening their data. We will highlight how policies, protocols and processes are equally important components for opening data in addition to infrastructure and digital repositories.